2011
DOI: 10.1007/s12471-011-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clinical outcomes of Chinese sirolimus-eluting stents versus foreign sirolimus-eluting stents for the treatment of coronary artery disease

Abstract: Chinese SES and foreign SES have similar effects on 1-year clinical outcomes and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The results of the long-term clinical follow-up revealed that the restenosis rate for the YINYI™ stent within two and six months postoperatively was 4 and 1.25%, respectively. This was similar to the results obtained in previous studies (22,23), which indicated that the early restenosis rate was 5% and that the restenosis rate in the clinical follow-up was relatively low.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the long-term clinical follow-up revealed that the restenosis rate for the YINYI™ stent within two and six months postoperatively was 4 and 1.25%, respectively. This was similar to the results obtained in previous studies (22,23), which indicated that the early restenosis rate was 5% and that the restenosis rate in the clinical follow-up was relatively low.…”
Section: Discussionsupporting
confidence: 92%